Killer Mothers: The Legal Construction of Infanticide and Honor in Mexico in the Nineteenth and Twentieth Centuries. - Esqueda, Martha Santillán (Journal of Social History)
The penal conceptualization of infanticide (understood as the murder of a newborn) in the 1871 Federal Penal Code resulted from the construction of the liberal patriarchal state. Two interrelated phenomena justified the inclusion of infanticide in Mexican criminal law: the legal value of female sexual honor and the differentiated legal protection of the newborn's life, depending on its legitimate or illegitimate quality. The offense of infanticide remained very similar in its definition and penalties in subsequent federal codes (1929 and 1931) until its repeal in 1994. During this period, alongside that conceptual stability, there were changes in criminological, judicial, and social views about infanticide, motherhood, and female sexuality. The repeal in 1994 was the result of a series of social and political changes rather than judicial interest. The focus of this article is to analyze legal conceptions of infanticide in various criminological and legal texts to show how they changed from the Siete Partidas to 1994. It is possible to observe that the ideas about newborn life and their relation to female honor and, ultimately, to ideals of motherhood were compatible with the interests defended by the liberal state that resisted social transformations.